THE  18O OF PHOSPHATE OF ANCIENT HUMAN BIOGENIC APATITE CAN REALLY BE USED FOR QUANTITATIVE PALAEOCLIMATE RECONSTRUCTION? - Iacumin, Paola; Venturelli, Giampiero (European Scientific Journal, ESJ, 2015)
It is well known that the oxygen isotope composition of phosphate apatite (δph) in mammal bones and teeth is strongly correlated to that of the drinking water (δw) ingested by the mammal itself. However, the relation between (δph) and (δw) has to be considered with caution when used for palaeoclimate reconstruction because of the uncertainty of the data. Usually, however, the authors underestimate this problem, that may led to misleading results. On the basis of the phosphate - water data existing in the literature for humans, we estimated that the prediction uncertainty for δw calculated from a new value of δph is on the order of 2.5‰. It means that only in the case the difference between two calculated δw values is higher than about 3- 4‰, the δw values may be considered significantly different. This represents a big limit which cannot be underestimated in the use of human δph for prediction of single δw values and subsequent estimation of palaeotemperature. A similar evaluation would be performed also for other mammals.